Volcanogenic CO2 Degassing in the Songliao Continental Rift System, NE China. (19th August 2019) - Zhao, Wenbin; Guo, Zhengfu; Lei, Ming; Zhang, Maoliang; Ma, Lin; Fortin, Danielle; Zheng, Guodong
Abstract : The Wudalianchi monogenetic volcanic field (WMVF) is located in the Songliao basin within a major continental rift system in NE China. Bubbling springs and diffuse degassing from soils are typical features of the WMVF. Chemical compositions and C-He isotope analyses revealed that the cold spring gases might originate from the enriched upper mantle (EM), which resulted from the mixing between slab materials (subducted organic sediments and carbonates) in the mantle transition zone (MTZ) and the ambient depleted mantle. These EM-derived volatiles experienced variable degrees of crustal input, including both continental organic metasediments and crustal carbonates during their ascending path to the surface. The estimated results of the degassing CO2 fluxes, combined with previous geophysical evidence, suggest that the CO2 degassing activities become weaker from early to late in Quaternary.